Conservative Management of Non-Traumatic Spontaneous Bilateral Deep Intracerebral Hemorrhage: Neurological Perspectives from Two Cases - Indah Nurul Maghfiroh (International Medical Journal Corp. Ltd, 2026)
Introduction: Non-traumatic spontaneous bilateral intracerebral hemorrhage (PISBNT) is a rare subtype of hemorrhagic stroke and is often perceived as having a poor prognosis. Accurate etiological assessment and appropriate management are critical to guide clinical decision-making. Case Illustration: We report two cases of PISBNT. The first involved a 34-year-old man presenting with acute right-sided hemiparesis and dysarthria, found to have bilateral lentiform nucleus hemorrhages. The second was a 65-year-old woman with left-sided hemiparesis and dysarthria, with bilateral thalamic hemorrhages. Both patients presented with elevated blood pressure. Non-contrast CT confirmed bilateral deep intracerebral hemorrhage, while CT angiography excluded secondary vascular causes. No mass effect or intraventricular extension was observed. Discussion: Both patients were managed conservatively with strict blood pressure control and comprehensive stroke unit care. Structured etiological reasoning supported hypertension as the primary cause. Despite bilateral involvement, neurological status improved progressively during hospitalization. Follow-up imaging at six months demonstrated complete hematoma resorption, and both patients achieved favorable functional outcomes (mRS 1). Conclusion: PISBNT does not inevitably predict poor outcome. When guided by systematic neurological assessment and conservative management, selected patients can achieve excellent recovery. These cases highlight the importance of individualized clinical reasoning in managing rare bilateral intracerebral hemorrhage.